2005
DOI: 10.1242/dev.02140
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafishvps33b, an ortholog of the gene responsible for human arthrogryposis-renal dysfunction-cholestasis syndrome, regulates biliary development downstream of the onecut transcription factorhnf6

Abstract: SummaryZebrafish vps33b, an ortholog of the gene responsible for human arthrogryposis-renal dysfunction-cholestasis syndrome, regulates biliary development downstream of the onecut transcription factor hnf6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 28 publications
(4 reference statements)
4
57
1
Order By: Relevance
“…This keratin pattern resembled the ectopic cytokeratin expression observed in hepatocytes of Hnf6-deficient mice (Clotman et al, 2002) and is also present in the livers of zebrafish larvae at the onset of biliary development ( Fig. 3L; see also Lorent et al, 2004;Matthews et al, 2004Matthews et al, , 2005. Since hepatocytes are the principal non-biliary cells in the 5-dpf zebrafish liver, it is likely that the non-biliary immunoreactive keratin is present in these cells (as reported for Hnf6-deficient mice).…”
Section: Antisense Knockdown Reveals a Role For Onecut3 In Zebrafish supporting
confidence: 75%
See 2 more Smart Citations
“…This keratin pattern resembled the ectopic cytokeratin expression observed in hepatocytes of Hnf6-deficient mice (Clotman et al, 2002) and is also present in the livers of zebrafish larvae at the onset of biliary development ( Fig. 3L; see also Lorent et al, 2004;Matthews et al, 2004Matthews et al, , 2005. Since hepatocytes are the principal non-biliary cells in the 5-dpf zebrafish liver, it is likely that the non-biliary immunoreactive keratin is present in these cells (as reported for Hnf6-deficient mice).…”
Section: Antisense Knockdown Reveals a Role For Onecut3 In Zebrafish supporting
confidence: 75%
“…The morpholinos targeted the translation initiation codon or the splice acceptor of the second exon of the oc3 gene (Table 1). To measure the effect of the knockdowns on biliary development, we examined intrahepatic bile duct anatomy and biliary secretion, as determined by gallbladder fluorescence following ingestion of PED6, a fluorescent phospholipid (Farber et al, 2001;Matthews et al, 2004Matthews et al, , 2005. Keratin immunohistochemistry, which delineates bile ducts in zebrafish larvae Matthews et al, , 2005, demonstrated altered duct morphology in over 95% of 5-dpf morpholino-injected larvae analyzed ( Fig.…”
Section: Antisense Knockdown Reveals a Role For Onecut3 In Zebrafish mentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, the intrahepatic biliary network is formed by small-diameter ductular biliary epithelial cells, which might be analogous to small-diameter ductular biliary epithelial cells in the mammalian liver lobule that transport bile from the canalicular network to the intralobular bile ducts in the portral tract (Kaneko et al, 2015). Indeed, there is remarkable conservation of both genes and gene function across vertebrate biliary system development, and thus many candidate genes responsible for biliary system abnormalities in humans can be screened efficiently and rapidly in the zebrafish model Delous et al, 2012;Hand et al, 2009;Lorent et al, 2015Lorent et al, , 2010Lorent et al, , 2004Matthews et al, 2011Matthews et al, , 2005Sakaguchi et al, 2008;Schaub et al, 2012). The zebrafish transgenic line Tg(Tp1-MmHbb: EGFP) um14 , which is generated by conjugating tandem RBPJκ response element repeats with enhanced green fluorescent protein (EGFP), expresses EGFP specifically in the intrahepatic biliary network in the zebrafish liver (Lorent et al, 2010;Parsons et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many mutant phenotypes are reminiscent of human disease and have proved invaluable in deciphering signaling cascades implicated in cardiovascular (3,19), renal (20), and gastrointestinal biology (21) and in cancer (22). Initial forward genetic screens have phenotyped embryos based on morphology as optical clarity during external zebrafish embryogenesis facilitates visual analysis during their rapid development (6).…”
mentioning
confidence: 99%